2009
DOI: 10.1007/s10750-009-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in zooplankton community between River Drawa and its two tributaries (Polish part of River Odra)

Abstract: Zooplankton communities were studied in a river and its tributaries with different hydrological, biological and physico-chemical conditions. Small similarities were noted in the zooplankton community (mostly Rotifera) between a tributary characterised by a regular bed and the river. No influence of a tributary with an irregular bed and variable water flow was noted on the zooplankton of the river it joined. It was concluded that the tributaries had very little influence on the zooplankton community in the rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
2
26
0
1
Order By: Relevance
“…In the lower course of each outlet, no significant reduction in the abundance, biomass or body size of rotifers was observed. In rivers, especially in their lower sections, the abundance of rotifers is usually large (Chang et al 2008, Czerniawski & Domagała 2010b. Perhaps planktivorous fish, which mainly reduce the abundance of zooplankton (Armitage & Capper 1976, Sandlund 1982, selected larger specimens and in this way did not influence the abundance of small rotifers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the lower course of each outlet, no significant reduction in the abundance, biomass or body size of rotifers was observed. In rivers, especially in their lower sections, the abundance of rotifers is usually large (Chang et al 2008, Czerniawski & Domagała 2010b. Perhaps planktivorous fish, which mainly reduce the abundance of zooplankton (Armitage & Capper 1976, Sandlund 1982, selected larger specimens and in this way did not influence the abundance of small rotifers.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al (2005) and Czerniawski & Domagała (2010b) also proved that different hydrological and biological conditions of small rivers differently affect the formation of a zooplankton community in the downstream section. So it appears that a reduction in a zooplankton community in the outlets and streams with different hydrological conditions may also be different, despite the same trophic status of lakes from which watercourses flow out.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors studying the influence of hydrological conditions of outlets or streams on the composition of zooplankton have reported a positive correlation between hydrological variables and communities of plankters, especially the large taxa (Campbell 2002, Czerniawski & Domagała 2012. Perhaps, in the outflow sections where current velocity and discharge are high, the pressure of planktivorous fish on zooplankton is smaller, because of high current speed that drifts zooplankton faster, making it hard to reach (Czerniawski & Domagała 2010b). Therefore, one can conclude that the influence of hydrological parameters on the biomass of zooplankton in the outlets is the opposite of their influence in rivers.…”
Section: Discussionmentioning
confidence: 99%
“…According to Czerniawski & Domagała (2010a) the reduction of zooplankton in the outflows from mesotrophic lakes is faster than in the outflows from eutrophic lakes. Other studies (Campbell 2002, Czerniawski & Domagała 2010b have suggested that increases in hydrological parameters and vegetation coverage have a positive impact on the abundance and decreased rate of reduction of zooplankton in rivers.…”
Section: Introductionmentioning
confidence: 96%